The influences of human resource practices on employee retention in electronic manufacturing service, Penang - Brendaline, S. Anncelia (2021)
Every organization has their own objectives and aims but most of the organization tries hard as their main objective will always be to handpick the right candidate for the right job by enthralling and retaining them in the organization. In today’s situation with the pandemic, retaining employees has become crucial and important. The main idea of this research is to explore and investigate on the human resource practices that affect employee retention such as employee empowerment, performance appraisal and compensation. The data were compiled from the 5-point Likert scale questionnaires which were distributed to 120 engineers in Penang through the google form. A total of 93 questionnaires were collected from the 120 respondents and from the analysis done, the results shows that from the three variables (employee empowerment, performance appraisal and compensation) only two variables (performance appraisal and compensation) is significant and has positive influences on employee retention. The findings from this study is adequate to be used as references by companies and this also can help the management especially human resource department to be aware and take all the necessary steps to retain employees.